Peran Pemerintah dalam Pengendalian Alih Fungsi Lahan dan Eskalasi Kerugian Ekonomi Akibat Banjir di Sumatra - Ahmad Wahyudi Zein; Demala Sari; Aprilia Regitasya Parinduri; Ika Wahyu Indriani Ningsih; Al Habib Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Flooding remains one of the most recurrent hydrometeorological disasters in Sumatra and has generated substantial economic and social consequences for regional development and community welfare. One of the dominant factors intensifying flood occurrences is the uncontrolled conversion of land use, particularly the transformation of forest areas, wetlands, and water catchment zones into settlements, large-scale plantations, and economic infrastructure. This study aims to examine the government’s role in regulating land-use change and its implications for the escalation of economic losses caused by flooding in Sumatra, viewed from the perspective of Islamic macroeconomics. The research employs a descriptive qualitative approach by utilizing secondary data obtained from official reports published by the National Disaster Management Agency (BNPB), the Central Statistics Agency (BPS), and the Ministry of Environment and Forestry (KLHK), as well as relevant academic literature. The findings indicate that poorly regulated land-use change has significantly contributed to the increasing frequency and severity of flooding, leading to infrastructure damage, reduced agricultural productivity, disruption of economic activities, and rising fiscal pressure on local governments. Weak institutional supervision, inconsistency in spatial planning policies, and ineffective law enforcement have limited the government’s ability to mitigate these impacts. From the perspective of Islamic macroeconomics, these conditions contradict the principles of trust (amanah), public interest (maslahah), and the objectives of Islamic law (maqashid al-shariah), particularly in safeguarding wealth and human life. Therefore, strengthening governmental control over land-use change through policies grounded in justice, environmental sustainability, and public welfare is essential to reduce flood risks and minimize economic losses in Sumatra.